Simplify (a⁷/a⁵) × (a⁻²/a⁻⁴) + (a⁷)³: Complete Exponent Expression

Question

Simplify the following expression:

a7a5×a2a4+(a7)3= \frac{a^7}{a^5}\times\frac{a^{-2}}{a^{-4}}+(a^7)^3=

Video Solution

Solution Steps

00:00 Simplify the following expression
00:03 When dividing powers with equal bases
00:07 The power of the result equals the difference between the exponents
00:11 We'll apply this formula to our exercise, and subtract the exponents
00:40 When multiplying powers with equal bases
00:44 The power of the result equals the sum of the exponents
00:47 We'll apply this formula to our exercise, and add together the exponents
01:01 When there's a power raised to a power, the result will be the product of exponents
01:08 We'll apply this formula to our exercise, and multiply the exponents
01:17 This is the solution

Step-by-Step Solution

a. Let's start by working on the first expression from the left, which is a multiplication of fractions. However, we won't perform the fraction multiplication; instead notice that in each of the fractions in the multiplication, there are terms in both the numerator and denominator with identical bases.

Therefore we'll apply the power law for division between terms with identical bases:

cmcn=cmn \frac{c^m}{c^n}=c^{m-n}

We'll apply this to our problem in the first expression from the left and apply the above power law separately to each term in the fraction multiplication:

a7a5a2a4=a75a2(4)=a2a2+4=a2a2 \frac{a^7}{a^5}\cdot\frac{a^{-2}}{a^{-4}}=a^{7-5}\cdot a^{-2-(-4)}=a^2\cdot a^{-2+4}=a^2\cdot a^2

Note that we have an algebraic expression that is in fact the term multiplied by itself, therefore we can write the expression as a power:

a2a2=(a2)2 a^2\cdot a^2=(a^2)^2

(Of course we could also apply the multiplication law between terms with identical bases to the above expression, but here we want to make use of the power of a power law, so we'll choose this way instead),

Now let's recall the power of a power law:

(cm)n=cmn (c^m)^n=c^{m\cdot n}

and apply it to the expression that we obtained:

(a2)2=a22=a4 (a^2)^2=a^{2\cdot2}=a^4

We've finished handling the first expression from the left as shown below:

a7a5a2a4=a4 \frac{a^7}{a^5}\cdot\frac{a^{-2}}{a^{-4}}=a^4

Remember this result and move on to the next expression.

b. For the second expression from the left, we'll once again apply the power of a power law mentioned in section a:

(a7)3=a73=a21 (a^7)^3=a^{7\cdot3}=a^{21}

Let's combine both solutions (a and b) into the simplified expression as follows:

a7a5a2a4+(a7)3=a4+a21 \frac{a^7}{a^5}\cdot\frac{a^{-2}}{a^{-4}}+(a^7)^3=a^4+a^{21}

Therefore the correct answer is b.

Answer

a4+a21 a^4+a^{21}